ChemInform Abstract: Bismuth‐Catalyzed Synthesis of Polycyclic Aromatic Hydrocarbons (PAHs) with a Phenanthrene Backbone via Cyclization and Aromatization of 2‐(2‐Arylphenyl)vinyl Ethers. Issue 7 (29th January 2015) - Murai, Masahito; Hosokawa, Naoki; Roy, David; Takai, Kazuhiko
Abstract By choosing the appropriate catalytic system, the reaction can be used to synthesize phenanthrene derivatives with electron‐withdrawing and ‐donating substituents in various positions.